Efficacy, safety, and prognosis prediction in patients treated with ribociclib in combination with letrozole: final results of phase 3b RIBECCA study in hormone receptor positive, human epidermal growth factor receptor-2 negative, locally advanced or metastatic breast cancer - Fasching, Peter Andreas; Decker, Thomas; Hartkopf, Andreas; Nusch, Arnd; Heinrich, Bernhard J.; Kurbacher, Christian; Fuchs, Roswitha; Tesch, Hans; Krabisch, Petra; Huober, Jens; Kuemmel, Sherko; Brucker, Sara; et al. (European journal of cancer, 2024)
Background - In MONALEESA-2, addition of ribociclib to letrozole resulted in significantly longer progression-free survival (PFS) in postmenopausal women with HR+HER2− advanced breast cancer (ABC). RIBociclib for the treatment of advanCed breast CAncer (RIBECCA) study investigated ribociclib plus letrozole in a patient population reflecting routine clinical practice. - Patients and methods - In this multicenter, open-label, single-arm, phase 3b study, patients with HR+HER2− ABC not amenable to curative therapy and ECOG performance status ≤ 2 received ribociclib plus letrozole (cohort A: postmenopausal women and men in first-line; cohort B: pre-/perimenopausal women in first-line [B1], patients pretreated for advanced disease [B2]). The primary endpoint was clinical benefit rate (CBR) by week 24; secondary endpoints included overall response rate (ORR), PFS, overall survival (OS), and safety. Association of patient and tumor characteristics with PFS was analyzed by multivariable Cox regression analysis. - Results - Overall, 487 patients were evaluable for efficacy, 502 for safety. By week 24, CBR was 60.8 % (95 % CI, 56.3-65.1), ORR was 19.3 % (95 % CI, 15.9-23.1). Median PFS was 21.8 months (95 % CI, 13.9-25.3) in first-line postmenopausal patients and 11.0 months (95 % CI, 8.2-16.4) in premenopausal and pretreated patients. Median OS was not reached. Higher baseline ECOG performance status, higher histological grade, and negative progesterone receptor status showed an unfavorable effect on PFS. Most common adverse events were neutropenia (50.0 %), nausea (42.0 %), and fatigue (39.2 %). - Conclusion - In this broad population of patients with HR+HER2− ABC, efficacy and safety results of ribociclib plus letrozole were similar to those observed in pivotal trials.
Online veröffentlicht: 15 December 2023
Gesehen am 23.09.2024